PERAN UNDANG – UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN DALAM PERLINDUNGAN DAN PELESTARIAN OBJEK WISATA - Paramarta Jaya, I Wayan; Putra Ariana, I Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
The paper is titled "The Role of Law - Law No. 10 Year 2009 on tourism and preservation" By using normative research method of this paper describes how the role of law in the preservation of attractions. Indonesia is one of the world's tourist destination for its natural beauty. The natural beauty of this time has managed the business objectives for the welfare of the community itself in accordance with Article 33 paragraph (3) of the 1945 Constitution. The beauty is supposed to be protected and preserved for the purpose of sustainable tourism development.
Keywords: Beauty, Welfare, Development